Beyond Legitimation: A Tribal Response to Māori Education in Aotearoa New Zealand - Tomlins Jahnke, Huia (The Australian Journal of Indigenous Education, 2012)
This article describes an intervention strategy, initiated under the New Zealand Government's tribal partnership scheme, which promotes a culture-based/place-based approach to education in mainstream schools and early childhood centres in one tribal region. Through place-based education children are immersed in local heritage, including language and culture, landscapes, opportunities and experiences. The strategy is a tribal response to the overwhelming evidence of Māori underachievement in education in the tribal catchment. A case study is presented of a place-based/culture-based initiative called the Ngāti Kahungunu Cultural Standards Project (NKCSP). It is argued that the development of cultural standards offers an opportunity by which teachers and others within the education sector can develop and incorporate practice that reflects, promotes and values the student's culture. The core assumption underpinning the project is that cultural knowledge contributes to Māori student success in education.